Budesonide orodispersible tablets for induction of remission in patients with active eosinophilic oesophagitis: A 6‐week open‐label trial of the EOS‐2 Programme. Issue 3 (12th April 2022) - Miehlke, Stephan; Schlag, Christoph; Lucendo, Alfredo J.; Biedermann, Luc; Vaquero, Cecilio Santander; Schmoecker, Christoph; Hayat, Jamal; Hruz, Petr; Ciriza de los Rios, Constanza; Bredenoord, Albert Jan; Vieth, Michael; Schoepfer, Alain; et al.
Abstract: Background: A novel budesonide orodispersible tablet (BOT) has been proven effective in adult patients with active eosinophilic oesophagitis (EoE) in a 6‐week placebo‐controlled trial (EOS‐1). Aims: To report the efficacy of an open‐label induction treatment with BOT in a large prospective cohort of EoE patients within the EOS‐2 study. Methods: Patients with clinico‐histological active EoE were treated with BOT 1 mg BID for 6 weeks. The primary endpoint was clinico‐histological remission (≤2 points on numerical rating scales [0–10] each for dysphagia and odynophagia, and peak eosinophil count <16 eos/mm 2 hpf (corresponds to <5 eos/hpf)). Further study endpoints included clinical and histological remission rates, change in the EEsAI‐PRO score, change in peak eosinophil counts, and deep endoscopic remission using a modified Endoscopic Reference Score. Results: Among 181 patients enrolled, 126 (69.6%) achieved clinico‐histological remission (histological remission 90.1%, clinical remission 75.1%). The mean peak eosinophil counts decreased by 283 eos/mm 2 hpf (i.e., by 89.0%). Mean EEsAI‐PRO score decreased from baseline by 29 points and deep endoscopic remission was achieved in 97 (53.6%) patients. The majority of patients judged tolerability as good or very good (85.6%) and compliance was high (96.5%). Local candidiasis was suspected in 8.3% of patients; all were of mild severity, resolved with treatment and none led to premature withdrawal from the study. Conclusions: In this large prospective trial, a 6‐week open‐label treatment with BOT 1 mg BID was highly effective and safe in achieving clinico‐histological remission of active EoE and confirmed the results of the placebo‐controlled EOS‐1 trial.